HPA 201 E - Major Themes In Selected World Religions [Tema- Tema Utama Dalam Agama-Agama Dunia Terpilih] - November 2005 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (2005)
UNIVERSITI SAINS MALAYSIA First Semester Examination Academic Session 2005/2006 November 2005 HPA 201 E - Major Themes In Selected World Religions [Tema- Tema Utama Dalam Agama-Agama Dunia Terpilih] Duration: 3 hours [Masa: 3 jam] Please check that this examination paper consists of FIVE pages of printed material before you begin the examination.